Horse portraiture and blazing saddles - research report on the artist Emil Volkers (1831-1905) - Selke, Raimond; Gohl, Walter (Brukenthal National Museum, 2014)
Emil Volkers was a popular 19th century German horse portraitist. After Dresden Art Academy, he developed a unique style, and aristocrats provided commissions. He became "court painter" to Prince Charles of Romania, and was commissioned by William I to paint him on horseback. His paintings were popular with European rulers, as horses were important to their lifestyle. Volkers also painted rural and historical scenes. It is surprising that he is not generally acknowledged in art history literature, which contrasts with the number of his paintings sold today, and the number in private collections compared with the few held publicly. Lack of official recognition may be due to the few surviving documents plus the number of unknown collectors, which makes it difficult to produce an academic monograph. This paper aims to introduce Volkers to the international research community under the aforementioned aspects.